IMPLEMENTASI KEBIJAKAN PROGRAM KELUARGA BERENCANA (KB) DI KECAMATAN KOTA TENGAH KOTA GORONTALO - Stevani Laude; Asna Aneta; Ismet Sulila (Yayasan Panca Bakti Wiyata Pangandaran, 2024)
This study aims to investigate (1) the role of communication in the implementation of Keluarga Berencana Family planning program. Policy in Kota Tengah Sub-district, Gorontalo City, (2) the resources involved in the implementation of this policy; (3) the disposition of stakeholders in the policy implementation; and (4) the bureaucratic structure influencing the implementation of Keluarga Berencana in Kota Tengah Sub-district, Gorontalo City. This study employed a descriptive qualitative method and aimed to prove the effectiveness of Keluarga Berencana in Kota Tengah Sub-district, Gorontalo City. The findings indicate that the implementatition of Keluarga Berencana Policy in Kota Tengah Sub-district Office, and resource standards have not been identified, including challenges posed by the COVID-19 pandemic, which has altered critical elements, particularly among the target population. Consequently, the researcher posits that addressing Keluarga Berencana’s Challenges requires applying George C. Edwart III’s structured and efficient implementation theory. This entails the establishment of Standard Operating Procedures (SOPs) and performance standards for policy implementers, alongside ensuring that human resource needs are met in terms of quantity and the educational qualifications of personnel involved at the Kota Tengah Sun-district Office.